2005
DOI: 10.2169/internalmedicine.44.632
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of Primary Pulmonary Osteosarcoma

Abstract: Two cases of primary pulmonary osteosarcoma are presented. In both cases, chest computed tomography revealed a calcified pulmonary mass and technetium-99m methylene diphosphonate bone scintigraphy showed intense uptake in the pulmonary mass. Primary pulmonary osteosarcoma was suspected on the basis of these radiographic findings. Microscopic examination of tumor specimens obtained by needle biopsy revealed histologic features of osteosarcoma, and this diagnosis was confirmed by postmortem examination of a seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 15 publications
(20 reference statements)
1
18
1
Order By: Relevance
“…The patient was alive 42 months post pneumonectomy with extensive metastatic disease and morbidity. Lymph node metastasis is uncommon in this uncommon entity, with only 4 of the 21 reported cases having lymph node metastases [4][5][6][7], and only the aforementioned patient [4] received palliative radiotherapy. Loose [8] reported on a patient who received palliative radiotherapy for a resected brain metastasis and was alive 7 months after diagnosis with no evidence of disease.…”
Section: Discussionmentioning
confidence: 99%
“…The patient was alive 42 months post pneumonectomy with extensive metastatic disease and morbidity. Lymph node metastasis is uncommon in this uncommon entity, with only 4 of the 21 reported cases having lymph node metastases [4][5][6][7], and only the aforementioned patient [4] received palliative radiotherapy. Loose [8] reported on a patient who received palliative radiotherapy for a resected brain metastasis and was alive 7 months after diagnosis with no evidence of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Only 20 cases of primary osteosarcoma of the lung have previously been reported [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. We report the most recent case of primary osteosarcoma of the lung, which was diagnosed by computed tomography (CT)-guided needle biopsy, rapidly progressed, and was later confirmed by autopsy examination.…”
Section: Introductionmentioning
confidence: 99%
“…To explain this, three possibilities were considered as follows: The first possibility is that the tumor was a mixed carcinoma and sarcoma. Primary pulmonary osteosarcomas are generally extremely rare, with only a few cases reported in the literature to date (1)(2)(3)(4)(5). The origin of the carcinoma in most cases of primary pulmonary carcinosarcoma is non-SCLC (8).…”
Section: Discussionmentioning
confidence: 99%
“…Primary pulmonary osteosarcoma is a rare entity, with only a few cases reported in the literature to date (1)(2)(3)(4)(5). Miller et al (6) reported the incidence of primary pulmonary osteosarcoma as 0.01%.…”
Section: Introductionmentioning
confidence: 99%